Today's health information management - McWay, Dana C. (Thomson Delmar Learning, 2008)
Specifically designed to reinforce and apply concepts and develop critical thinking, this workbook provides various exercises and case studies that strengthen the knowledge and skills of learners preparing to enter the health information management profession